The Duty of Adverse Drug Reaction Alerting from the Perspective of Laws, Current Practices, and Guidelines Related to a Comparative Rights Approach - milad mashayekh; vali eslami (پژوهشهای حقوقی)
From the point of view of production, the current era can be considered as the era of complex products, because we have passed from the era of traditional products to the industrial one and we are witnessing the strong role of industry in the current life of people from life to death. One of the examples of the expansion of industry can be It was clearly observed in the production and supply of pharmaceutical products. Products that are directly related to human health and life play a role in this sensitive valley. The lack of access for all to different biomes in order to obtain traditional medicines is definitely a matter of praise, especially if the producer goes through all the production steps well and without any defects, which will be highly appreciated. If the procedure is carried out properly, it still brings unwanted side effects, which of course, the extent of these side effects also has severity and weakness, and naturally its destructive effects are also different. In the upcoming article, Pira's Warning Duty we will pay attention to the unwanted side effects of medicine and in order to identify the person responsible for the warning, we will stick to the descriptive-normative method. The doctor's consensus has pointed out that we will explain and examine this issue in detail in the next article.